RANCANGAN SISTEM INFORMASI ANEMIA PADA PLATFORM ONLINE “SRIKANDI HEALTH” BERBASIS PROGRESSIVE WEB APPS - Puji Handayani Putri (Jurnal Sehat Mandiri, 2021)
Anemia is one of the nutritional problems that has the potential to hinder the development of the quality of Indonesian human resources. The support of science and information technology in the form of a website application can be a solution to facilitate education, monitoring and management of anemia so as to accelerate the handling of anemia. This study aims to design an anemia information system in the form of an online platform with the name "Srikandi Health" based on Progressive Web Apps to support the prevention of anemia in Indonesia in Indonesia. This research was conducted in December 2020 in Bantul, Yogyakarta. This study uses the prototype method. The stages of the prototype method start from gathering requirements, building prototyping, and evaluating protoptyping. The result of this research is the prototype of the online application "Srikandi Health" based on Progressive Web Apps. Conclusion Srikandi Health prototype is designed to meet the needs analysis of the system, namely to facilitate monitoring and prevention of anemia in adolescents.The suggestion of this research is the implementation of the system so that the system becomes more complete and can be applied to the wider community.